Penentuan Resistivitas Tak-Terkompensasi Cairan Ion Berbasis Imidazol dengan Metode EIS: Pengaruh Panjang Alkil dan Perbedaan Anion - Aep Patah; Yulia Rachmawati; Riyadini Utari; Achmad Rochliadi (Universitas Andalas, 2020)
Ionic liquids have interesting properties because they have several advantages compared to conventional organic solvents, such as high thermal stability, high viscosity, good solvent properties, non-flammable, and non-volatile. In electrochemistry, ionic liquids can be used as solvents without the addition of electrolytes. However, ionic liquids still have resistivity properties (uncompensated resistance), thus ohmic drop measurements are needed for a potential correction. Imidazole-based ionic liquids, which are known for their high conductivity and commonly used as a solvent, have been measured of their resistivity as a function of temperature, and type of their cations/anions. Electrochemical Impedance Spectroscopy (EIS) method was chosen to measure the resistivity of ionic liquids and Bode plot was generated for the analysis of the results. The measured resistivities of ionic liquids are in the range of 420 to 1500 ohm. It is concluded that the resistivity of the imidazole-based ionic liquid is influenced by the size of their constituent ions, the viscosity, and the resistance is decreased with increasing temperature.